Search for an excited lepton that decays via a contact interaction to a lepton and two jets in proton-proton collisions at root s=13 TeV - KAYA, MİTHAT (My University, 2020)
Results are presented from a search for events containing an excited lepton (electron or muon) produced in association with an ordinary lepton of the same flavor and decaying to a lepton and two hadronic jets. Both the production and the decay of the excited leptons are assumed to occur via a contact interaction with a characteristic energy scale ?. The branching fraction for the decay mode under study increases with the mass of the excited lepton and is the most sensitive channel for very heavy excited leptons. The analysis uses a sample of proton-proton collisions collected by the CMS experiment at the LHC at root s = 13 TeV, corresponding to an integrated luminosity of 77.4 fb(-1). The four-body invariant mass of the two lepton plus two jet system is used as the primary discriminating variable. No significant excess of events beyond the expectation for standard model processes is observed. Assuming that ? is equal to the mass of the excited leptons, excited electrons and muons with masses below 5.6 and 5.7 TeV, respectively, are excluded at 95% confidence level. These are the best limits to date.
Keywords: Fizik; Temel Parçacıklar ve Alanlar; Temel Bilimler; Physics; Basic Particles and Areas; Natural Sciences; FİZİK, PARÇACIKLAR VE ALANLAR; Temel Bilimler (SCI); PHYSICS, PARTICLES & FIELDS; PHYSICS; Natural Sciences (SCI); Beyond Standard Model; Hadron-Hadron scattering (experiments); COMPOSITE MODELS; PP COLLISIONS; QUARKS; HEAVY; Beyond Standard Model; Hadron-Hadron scattering (experiments)